Laryngeal and pleural ultrasound and acoustic radiation force impulse elastography in dogs with brachycephalic obstructive airway syndrome - Rein, Ariadne; Facin, Andréia Coutinho; de Almeida Fabris, Isabella; Lima, Bruna Bressianini; Gasser, Beatriz; Aires, Luiz Paulo Nogueira; Uscategui, Ricardo Andres Ramirez; Feliciano, Marcus Antônio Rossi; Moraes, Paola Castro (Scientific reports, 2025)
This study aimed to evaluate the pleural thickness, stiffness, and laryngeal stiffness in dogs clinically affected by brachycephalic obstructive airway syndrome using B-mode ultrasound and acoustic radiation force impulse elastography. Fifty-two brachycephalic pugs and French bulldogs, clinically classified as having brachycephalic obstructive airway syndrome (BOAS) grades 0, I, II, and III, were included, and 15 mesocephalic beagle dogs were used as the control group (CO). All animals underwent B-mode ultrasonography and subsequent elastography of the pleura and arytenoid cartilage of the larynx. Brachycephalic dogs showed greater pleural thickness than the control group dogs ( p = 0.008) and a trend toward lower pleural shear wave velocity was observed in brachycephalic dogs compared to CO ( p = 0.18). The larynx shear wave velocity was similar between types of skull and BOAS grades ( p = 0.80). Measurements of the pleural line thickness and pleural stiffness showed moderate capacity for diagnosing brachycephalic syndrome ( p = 0.01, cut-off value of > 0.82 mm and p = 0.04, cutoff value 3.29 m/s). The results suggest a secondary change in inspiratory effort at the tissue level of the pleura in dogs clinically affected by BOAS, which can be identified by B-mode ultrasound and elastography methods; however, it was not possible to diagnose changes in the arytenoid cartilage.